Promoting Inclusive Entrepreneurship for Marginalized Community in Post Pandemic Situation (American Journal of Management, 2021)
Since COVID-19 was first discovered, it has had ripple effects with devastating impacts on global economies and supply chains. It has once again highlighted the disproportionate concentration of economic opportunities in country’s urban areas. The solution lies in embracing the future and working towards strengthening the economy through an inclusive approach and focus on creating entrepreneurs from marginalized communities. Over the last decade there has been some increase in number of Scheduled Castes and Scheduled Tribes owned enterprises, these need to increase substantially to enable the socioeconomic empowerment of the marginalized communities. To achieve the vision Government of India has proposed schemes with special focus towards the inclusion of marginalized communities and regionally under-represented areas in entrepreneurship development programs. The major focus of the current study is to determine the challenges faced by entrepreneurs from marginalized communities against the backdrop of the pandemic and explore avenues to ensure their economic sustainability.
Keywords: management; entrepreneurship development; marginalized communities; India